Notes on tensor models and tensor field theories - Gurǎu, Rǎzvan (Arxiv, 2019)
Tensor models and tensor field theories admit a $1/N$ expansion and a melonic large $N$ limit which is simpler than the planar limit of random matrices and richer than the large $N$ limit of vector models. They provide examples of analytically tractable but non trivial strongly coupled quantum field theories and lead to a new class of conformal field theories. We present a compact introduction to the topic, covering both some of the classical results in the field, like the details of the $1/N$ expansion, as well as recent developments. These notes are loosely bases on four lectures given at the Journ\'ees de physique math\'ematique Lyon 2019: Random tensors and SYK models.
Version 1 vom 8. Juli 2019, Version 2 vom 15. Juli 2019
Gesehen am 06.10.2022